Determinação voltamétrica do nedocromil de sódio utilizando eletrodo de carbono vítreo - Rosa, T. F. [UNESP]; Saczk, A. A. [UNESP]; Zanoni, Maria Valnice Boldrin [UNESP]; Stradiotto, Nelson Ramos [UNESP] (Editora Unesp, 2003)
Estudos eletroanalíticos foram realizados com o Nedocromil de Sódio empregando as técnicas voltamétricas de varredura linear, pulso diferencial e onda quadrada, em tampão Britton-Robinson (pH 4,0). No estudo voltamétrico empregando a modalidade de varredura linear observou-se dois picos catódicos, irreversíveis, nos valores de potencial de -0,86 V e -1,10 V (vs ECS). As correntes de pico catódicas apresentaram um controle difusional segundo a relação Ipc versus v½. A dependência de Ipc com a concentração apresentou linearidade entre 5,0x10-4 mol L-1 e 5,0x10-3 mol L-1, limite de detecção de 8,2x10-5 mol L-1 e sensibilidade de 6,3x10³ mA/ mol L-1. Na voltametria de pulso diferencial o Nedocromil de Sódio apresentou dois picos catódicos, irreversíveis, nos valores de potencial de -0,67 V e -0,75 V (vs ECS). Curvas analíticas foram obtidas no intervalo de 3,0x10-6 mol L-1 a 1,0x10-5 mol L-1, limite de detecção de 4,9x10-7 mol L-1 e sensibilidade de 8,7x10(4) mA/ mol L-1. Na voltametria de onda quadrada observou-se dois picos catódicos nos valores de potencial de -0,80 V e -0,91 V (vs ECS), linearidade de 5,0x10-7 mol L-1 a 1,0x10-5 mol L-1, com limite de detecção e uma sensibilidade de 2,7x10-6 mol L-1 e 1,1x10(6) mA/ mol L-1, respectivamente.

Electroanalytical studies had been carried with the Nedocromil Sodium, an antiasthmatic drug, using the techniques of Linear Scan, Diferencial-Pulse and Square Wave Voltammetry. The technique of Linear Scan Voltammetry was used for determination of Nedocromil Sodium, at a glassy carbon electrode, in pH 4 Britton-Robinson buffer. Two irreversible reduction peaks where obtained in the values of potential of 0,86 V and 1,1 V. Calibration graphs were shown to be linear in the range 5,0x10-4 - 5,0x10-3 mol L-1. The coefficients of linear correlation have been equal to 0,9990, being the detection limit equal to 8,2x10-5 mol L-1 and the amperometric sensitivity equal to 6,3x10³ mA/ mol L-1. Diferencial-Pulse Voltammetry two irreversible reduction peaks were obtained at the values of potential of -0.67 V and -0.75 V. The study of the dependence of Ipc with the concentration of the solution showed linearity in the range 3,0x10-6 - 1,0x10-5 mol L-1, with coefficient of linear correlation of 0,9990. The detection limit was calculated to be 4,9x10-7 mol L-1, being the amperometric sensitivity equal to 8,7x10(4) µA/ mol L-1. The technique of Square Wave Voltammetry was used for the studies of the Nedocromil Sodium in the range 5,0x10-7 - 1,0x10-5 mol L-1. Two irreversible reduction peaks where obtained in the values of potential of 0,80 V and 0,91 V. The coefficients of linear correlation have been equal to 0,9748, being the detection limit equal to 2,7x10-6 mol L-1 and the amperometric sensitivity equal to 1,1x10(6) µA/ mol L-1.
Voltammetric determination of necrodil sodium using glassy carbon electrode
Keywords: nedocromil de sódio; voltametria de varredura linear; voltametria de pulso diferencial; voltametria de onda quadrada; asma; nedocromil sodium; linear scan voltammetry; diferencial-pulse voltammetry; square wave voltammetry; asthma